High-Risk Pregnancies and Their Impact on Neonatal Primary Hemostasis - Politou, Marianna; Mougiou, Vasiliki; Kollia, Maria; Sokou, Rozeta; Kafalidis, Georgios; Iliodromiti, Zoi; Valsami, Serena; Boutsikou, Theodora; Iacovidou, Nicoletta (Seminars in Thrombosis and Hemostasis, 2020)
Primary hemostasis, similar to other systems in the adjusting and transitioning neonate, undergoes developmental adaptations in the first days of life. Although platelets of neonates do not differ quantitatively compared with those of adults, they functionally present with major differences, thus supporting the theory of a “hypofunctional” phenotype that is counterbalanced by high hematocrit and more potent von Willebrand factor multimers. No clinical effect of bleeding tendency has hence been established so far for healthy term neonates. However, discrepancies in functionality have been noted, associated with gestational age, with more pronounced platelet hyporesponsiveness in preterm neonates. Multiple methods of in vitro platelet function evaluation such as PFA-100/200, platelet aggregometry, flow cytometry, and cone and platelet analyzer have been used for assessment of neonatal primary hemostasis. Several pregnancies are characterized as “high-risk” when risk factors preexist in maternal history or evolve during pregnancy. These pregnancies require specialized observation as they may have unpredictable outcome. High-risk pregnancies include clinical entities such as preeclampsia, pregnancy-induced smoking during pregnancy, gestational diabetes mellitus (GDM), autoimmune diseases, and other maternal hematological conditions. In some cases, like systemic lupus erythematosus, antiphospholipid antibody syndrome, and maternal immunologically based thrombocytopenia, neonatal thrombocytopenia is regarded as a prominent hemostasis defect, while in others, like pregnancy-induced hypertension and preeclampsia, both quantitative and qualitative disorders of neonatal platelets have been reported. In other pathologies, like GDM, neonatal primary hemostasis remains vastly unexplored, which raises the need for further investigation. The extent to which primary hemostasis is affected in neonates of high-risk pregnancies is the main objective of this narrative review.
Keywords: platelets; platelet function; neonates; primary hemostasis; high-risk pregnancies; neonatal hemostasis